The Comparative Effectiveness of Angiotensin‐Converting Enzyme Inhibitors and Angiotensin II Receptor Blockers in Patients With Diabetes. Issue 3 (19th August 2015) - Padwal, Raj; Lin, Mu; Eurich, Dean T.
Abstract : The evidence examining the effect of angiotensin‐converting enzyme (ACE) inhibitors and angiotensin receptor blockers (ARBs) on mortality in high‐risk patients is conflicting. To further examine this controversy, the authors compared outcomes between ACE inhibitors and ARBs in a large clinical diabetes registry. A retrospective cohort of 87, 472 incident users followed for 105, 702 patient‐years was analyzed. Average age was 53.1±10.1 years, 54.2% were men, and 14.4% had cardiovascular disease. All‐cause hospitalization or all‐cause mortality, the composite primary endpoint, occurred in 10, 943 (12.5%) patients. Compared with ACE inhibitors, the adjusted hazard for ARBs was 0.90 (95% confidence interval, 0.87–0.94) for all‐cause hospitalization or mortality; 0.95 (0.65–1.40) for mortality; 0.90 (0.87–0.94) for all‐cause hospitalization; and 0.81 (0.74–0.89) for cardiovascular admission. ARB use was associated with a reduced, not increased, risk of hospitalization/mortality relative to ACE inhibition. This was driven by lower hospitalization, with a null mortality result.